Epidemiology of Type-II Diabetes and its Risk Factors in Punjab, Pakistan: A Retrospective Study - Rana Mateen; Asma Tariq; Mureed Hussain; Muhammad Irfan Fareed; Waseem Sajjad; Imran Tipu; Rukhsana Parveen (Scientific Inquiry and Review, 2023)
Type-II diabetes is the most common type of diabetes, which has affected more than 465 million people globally and has become the ninth leading cause of mortality. The current study aims to determine risk factors associated with type-II diabetes such as BMI, cholesterol levels, physical activity, and smoking along with co-morbidities associated with this disease. The data was collected from the province of Punjab, Pakistan. For this purpose, a survey was performed for investigating the prevalence of type II diabetes and associated risk factors combined with it. A sample size of 265 patients was collected and interviewed through a questionnaire who were observed having type-II diabetes. A questionnaire was designed to record these patients’ responses. The questionnaire contained sub-categorizes, such as participants characteristics, lifestyle, and comorbidities associated with the disease. The findings indicated that the mean BMI was 25.62 in the studied cohort. However, 78% of the patients had a family history of diabetes. Moreover, 76% of the participants were reported to be non-smokers and 75.67% of the participants reported atypical features associated with this disease. It was also observed that 13 % of the patients with low BMI (less than 18.5) had gastrointestinal diseases and 14.72% of the patients with a BMI greater than 18.5 but less than 25 had hypertension, and 8.30 % of the patients with more than 30 BMI also had hypertension. High BMI was found to be a major risk factor associated with type-II diabetes in this study population. The patients observed with high BMI were also more prone towards comorbidities associated with this disease. However, data suggested that most of the patients had familial type-II diabetes.